Irish Migration: Characteristics, Causes and Consequences - Alan Barrett (Institute for the Study of Labor (IZA), 1999)
The purpose of this paper is to review what has been learnt about Irish migration from the work of social scientists, largely economists. For most of its modern history, Ireland has experienced large net outflows. I discuss how the outflow was made up of lower skilled people up until the 1980s but how more recent outflows have contained more highly skilled people. Over time, the outflow has also shown shifts in its gender make-up and in the destinations of those leaving. I review the work that has been done exploring the causes of the outflow. Generally, the low level of economic development in Ireland has been responsible; however, year to year fluctuations in the size of the outflows are associated with relative changes in Irish and British labour market conditions. Finally, I consider the work that has examined the effect of the large-scale outflows. While some have argued that the low level of development was partly a consequence of emigration, other work has shown that emigration helped to improve Irish living standards. I end with the observation that the research agenda is now changing as development, and net inflows, have emerged.
Keywords: J61; J15; 330; Migration; migration policy; Auswanderung; Qualifikation; Schätzung; Arbeitsmarkt; Einkommen; Irland